Advanced modeling of embedded piezo-electric transducers for the health-monitoring of layered structures - Enrico Zappino; Erasmo Carrera (International Journal of Smart and Nano Materials, 2020)
The present paper presents an innovative approach for the numerical modeling of piezo-electric transducers for the health-monitoring of layered structures. The numerical approach has been developed in the frameworks of the Carrera Unified Formulation. This computational tool allows refined numerical models to be derived in a unified and efficient fashion. The use of higher-order models and the capability to connect different kinematic models using the node-dependent kinematic approach has led to an efficient modeling technique for global-local analysis. This approach can refine the model only in those regions where it is required, e.g., the areas where piezo-electric transducers are placed. The model has been used to study embedded and surface-mounted sensors. The accuracy of the present model has been verified by comparing the current results with numerical and experimental data from the literature. Different modeling solutions have been developed, mixing one-, two- and three-dimensional finite elements. The results show that the use of the present modeling technique allows the computational cost to be reduced with respect to the classical approaches preserving the accuracy of the results in the critical areas.